PERSEPSI PASIEN TENTANG CARING BEHAVIOR PERAWAT DI RUANG ST. LAURA RUMAH SAKIT SANTA ELISABETH MEDAN TAHUN 2024 - Mestiana Br. Karo; Indra Hizkia P; Clara Alemyca (Bajang Institute, 2024)
Caring is defined as the core of nursing practice, namely, knowledge, fortitude, honesty, humility, trust, rhythm shifting, hope and strength, providing attention and focus, and respecting the lives of others as well as human lives. Nurses' caring behavior is shown by providing attention and care, as well as empathy for patients and families. To find out patients' perceptions of nurses' Caring behavior. This study uses a qualitative method, data collection is carried out through interviews, with 6 questions so that it is able to dig deeper into patients' perceptions of nurses' caring behavior. The sampling technique in this study uses purposive sampling with 5 participants selected based on rationality. The results of the study are obtained: Caring is the act of giving attention to others, caring by giving attention, sharing, helping each other, and giving strength to those who are sick. Caring behavior is the act of listening to and asking patient complaints, answering patient questions, and coming quickly when the patient needs it. Caring behavior is the presence of nurses by providing encouragement, radiating joy and excitement, and sharing with each other, so that patients have the spirit to recover to their previous condition. Caring behavior is the response of nurses shown through a friendly attitude, always smiling, and always giving greetings to patients and patients' families, both old and young nurses, and women and men who are done earnestly or whole heartedly. It is hoped that it can be used as information to increase knowledge about caring behavior